Development of Government Schools in Orangi Town, Karachi - Zafar, Sumaira; Qaisar, Maha; Sohail, Zainab; Zaidi, Arjumand (Journal of Geoscience, Engineering, Environment, and Technology, 2017)
The primary school system in Pakistan needs improvement in order to provide the basic right of education to all. Government schools are not enough to cater the needs of increasing population of the country. The main goal of this study was to present a methodology for the development of government schools based on geographical information system (GIS) through a case study of Orangi Town in Karachi. In this study, first the adequacy of government schools in the study area was evaluated and then the need for additional schools with their suitable locations were identified.  Data regarding school locations and students enrollments were collected from Sindh Basic Education Program of a non-profit NGO iMMAP. School building footprints were digitized from 2001 and 2013 Google Earth archived images. Population in 2013 was estimated by projecting 1998 census data downloaded from the website of the Census Bureau of Pakistan. An educated assumption of 20 % of the total population of Orangi Town was used to calculate number of primary school-aged children. Study results showed that schools existed in 2013 were not sufficient to serve all these children. This study also revealed that new schools were built during this time period, but the population growth rate was much higher than the growth rate of schools that created a big supply-demand gap. The most progressive Union Council (UC) of Orangi Town was Haryana Colony where 17 new schools were constructed between 2001 and 2013 though the required number of schools still fall short. New sites for schools were also proposed to optimally serve Orangi Town’s residents using GIS proximity analysis.